2019 IEEE International Conference on Image Processing (ICIP) 2019
DOI: 10.1109/icip.2019.8803665
|View full text |Cite
|
Sign up to set email alerts
|

Duodepth: Static Gesture Recognition Via Dual Depth Sensors

Abstract: Static gesture recognition is an effective non-verbal communication channel between a user and their devices; however many modern methods are sensitive to the relative pose of the user's hands with respect to the capture device, as parts of the gesture can become occluded. We present two methodologies for gesture recognition via synchronized recording from two depth cameras to alleviate this occlusion problem. One is a more classic approach using iterative closest point registration to accurately fuse point cl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…The authors reported state-of-the-art results using ModelNet40 shape classification benchmark. Further architectural extensions include PointNet++ [23], Temporal PointNet [24] for one-shot learning, and Dual PointNet for fusing information from two depth cameras [25].…”
Section: Introductionmentioning
confidence: 99%
“…The authors reported state-of-the-art results using ModelNet40 shape classification benchmark. Further architectural extensions include PointNet++ [23], Temporal PointNet [24] for one-shot learning, and Dual PointNet for fusing information from two depth cameras [25].…”
Section: Introductionmentioning
confidence: 99%